2013
DOI: 10.2147/ceor.s44325
|View full text |Cite
|
Sign up to set email alerts
|

The personal, societal, and economic burden of schizophrenia in the People's Republic of China: implications for antipsychotic therapy

Abstract: BackgroundThis article describes the personal, societal, and economic burden attributable to schizophrenia in the People’s Republic of China and highlights the potential for effective outpatient treatment to reduce this burden given recent changes in the Chinese health care system. The importance of effective antipsychotic therapy in reducing the burden of schizophrenia is also examined.MethodsPublished research on the burden, disability, management, and economic costs of schizophrenia in the People’s Republic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 99 publications
0
23
0
Order By: Relevance
“…These factors can also assist clinicians in the early identification of patients who may be appropriate candidates for weight management programs 69. Such programs may lower the risk of clinically significant weight gain during treatment with olanzapine and also provide additional clinical and functional benefits, including better treatment response and reduced impairment in work activities 4. Regarding the changes in metabolic parameters, the results observed in Chinese populations have been noted in numerous studies in non-Chinese populations 110,113.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These factors can also assist clinicians in the early identification of patients who may be appropriate candidates for weight management programs 69. Such programs may lower the risk of clinically significant weight gain during treatment with olanzapine and also provide additional clinical and functional benefits, including better treatment response and reduced impairment in work activities 4. Regarding the changes in metabolic parameters, the results observed in Chinese populations have been noted in numerous studies in non-Chinese populations 110,113.…”
Section: Discussionmentioning
confidence: 96%
“…A large-scale review estimated that the 1-month prevalence of any mental disorder among mainland Chinese is 17.5%, including a prevalence of mood disorders of 6.1% and a prevalence of psychotic disorders of 1.0% 2. In terms of addressing the challenge of chronic psychotic disorders, evidence from Chinese and non-Chinese populations suggests that effective treatment of psychotic disorders improves patient outcomes 3,4. However, synthesis of data from individual trials of antipsychotic agents to provide clinically useful recommendations for clinicians has mainly focused on non-Chinese populations 5…”
Section: Introductionmentioning
confidence: 99%
“…The personal, economic, and societal burden of schizophrenia is high, and when treated effectively, patients tend to persist longer with antipsychotic treatment, have fewer costly relapses, and have improved functioning 53. A recent analysis in Tianjin, People’s Republic of China, reported that patients with inpatient costs had almost ten times the cost of those without inpatient treatment 54.…”
Section: Discussionmentioning
confidence: 99%
“…It is costly to society due to its long course, high occurrence of comorbidities, necessity of hospitalizations and lack of a universally effective pharmacological treatment. Its prevalence is estimated to be between 0.3 and 1% worldwide (Mari & Leitão, 2000;Daltio et al, 2007;Messias et al, 2007;Montgomery et al, 2013). The main objective of the psychiatric hospitalization is to intervene in crisis and to control severely ill patients, ensuring their safety and of others patients (Marcolino, 2007).…”
Section: Introductionmentioning
confidence: 99%